IPF Marker as A differentiating Agent of Adult Thrombocytopenia Patients by Using Mindray Auto-Hematology Analyzer (1st attempt in Libya) - J M Jbireal; Seham Alzzahani (AlQalam Journal of Medical and Applied Sciences, 2025)
Platelets, crucial for hemostasis and thrombosis, are assessed in clinical practice using the immature platelet fraction (IPF), a marker reflecting bone marrow platelet production. IPF measurement, especially using automated hematology analyzers like Mindray BC-780[R], offers a non-invasive alternative for thrombocytopenia diagnosis. However, its utility in evaluating different thrombocytopenic conditions remains underexplored, particularly in Libya. The main aim is to evaluate the fraction of immature platelets in thrombocytopenia patients as compared with healthy individuals and the absolute immature count of platelets (AIPC). This descriptive, cross-sectional study included 228 participants (106 thrombocytopenic patients and 122 healthy controls) at Al-Wekaya Laboratory Center, Sabratha, Libya. Platelet counts and IPF were measured using the Mindray BC-780[R] analyzer. Statistical analyses were performed using SPSS v24 to evaluate differences in platelet parameters and IPF across various thrombocytopenia etiologies. Thrombocytopenic patients exhibited significantly lower platelet counts (70.5 × 10³/µL) and higher IPF (12.8%) compared to controls (258.1 × 10³/µL; IPF 4.23%; p < 0.001). Elevated IPF values (>10%) were prominent in hemolytic anemia (26.97%), acute myeloid leukemia (21.5%), and iron deficiency anemia (19.8%), indicating heightened bone marrow compensation. Pearson correlation revealed a significant inverse relationship between platelet count and IPF (r = -0.246, p = 0.011), highlighting compensatory platelet production in thrombocytopenic conditions. IPF measurement via Mindray BC-780[R] proves valuable for differentiating thrombocytopenia etiologies. Elevated IPF reflects active marrow compensation in conditions with heightened platelet turnover. This study, the first of its kind in Libya, emphasizes the clinical utility of automated IPF assessment in hematology. Further research is recommended to validate these findings across diverse populations and clinical settings.